Predicting Development of Glaucomatous Visual Field Conversion Using Baseline Fourier-Domain Optical Coherence Tomography - Zhang, Xinbo; Loewen, Nils; Tan, Ou; Greenfield, David S.; Schuman, Joel S.; Varma, Rohit; Huang, David; Huang, David; Francis, Brian; Greenfield, David S.; Parrish, Richard K.; Schuman, Joel S.; et al. (American journal of ophthalmology, 2016)
To predict the development of glaucomatous visual field (VF) defects using Fourier-domain optical coherence tomography (FD OCT) measurements at baseline visit. Multicenter longitudinal observational study. Glaucoma suspects and preperimetric glaucoma participants in the Advanced Imaging for Glaucoma Study. The optic disc, peripapillary retinal nerve fiber layer (NFL), and macular ganglion cell complex (GCC) were imaged with FD OCT. VF was assessed every 6 months. Conversion to perimetric glaucoma was defined by VF pattern standard deviation (PSD) or glaucoma hemifield test (GHT) outside normal limits on 3 consecutive tests. Hazard ratios were calculated with the Cox proportional hazard model. Predictive accuracy was measured by the area under the receiver operating characteristic curve (AUC). Of 513 eyes (309 participants), 55 eyes (46 participants) experienced VF conversion during 41 ± 23 months of follow-up. Significant (P < .05, Cox regression) FD OCT risk factors included all GCC, NFL, and disc variables, except for horizontal cup-to-disc ratio. GCC focal loss volume (FLV) was the best single predictor of conversion (AUC = 0.753, P < .001 for test against AUC = 0.5). Those with borderline or abnormal GCC-FLV had a 4-fold increase in conversion risk after 6 years (Kaplan-Meier). Optimal prediction of conversion was obtained using the glaucoma composite conversion index (GCCI) based on a multivariate Cox regression model that included GCC-FLV, inferior NFL quadrant thickness, age, and VF PSD. GCCI significantly improved predictive accuracy (AUC = 0.783) over any single variable (P = .04). Reductions in NFL and GCC thickness can predict the development of glaucomatous VF loss in glaucoma suspects and preperimetric glaucoma patients.